PERANAN KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP PERILAKU KARYAWAN - Teman Koesmono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
Managing human resource is part of one’s leadership design, therefore a leader plays an important role in leading his/her subordinates. There is not the best leadership style out of many types of leadership design, but the leadership design will be matched to the existing environment. All leadership designs will be led to company’s goal that has been established in which it is suitable with the company’s vision and mission. The company as the gathering place for one’s many characteristics will be in trouble if it doesn’t have a behavior guidance for everyone who gets involved in managing the organization. One’s behavior will be effected by stimulus occuring in one’s environment. The leader’s job is to establish the behavior guidance for all of the employees in the company, the behavior guidance mentioned is the organizational culture. Two very important things that must be paid attention seriously in leading employees’ behavior are Leadership Design and Organizational Culture as behavior guidance for all members in the organization.